2020
DOI: 10.11591/ijeecs.v18.i2.pp688-697
|View full text |Cite
|
Sign up to set email alerts
|

Power quality of dual two-level inverter fed open end winding induction motor

Abstract: <p><span>This paper presents the minimization of the total harmonic distortion (THD) of the current signal for open-end winding induction motor by using dual two-level inverter. In order to obtain a good value of THD, the space vector PWM has been used for switching the dual two-level inverter to improve the output voltage quality, gets a low common mode voltage, reduce the execution time, and to save the memory capacity. The proposed scheme uses two different DC voltage source with two two level i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The torque model proposed is realization block diagram [22]. The actual torque expression has been incorporated into the adaptive PI gain.…”
Section: Conventional Torque Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The torque model proposed is realization block diagram [22]. The actual torque expression has been incorporated into the adaptive PI gain.…”
Section: Conventional Torque Modelmentioning
confidence: 99%
“…Among many identification algorithms, the identification algorithm based on RASM is favored by people because of 1321 its easy implementation and good stability [1]. Many algorithms has different implementation forms depending on the selected physical quantity, such as q-axis rotor flux model [16], [17], d-axis stator voltage model [18], [19], reactive power model [1], [5], [20], [21], electromagnetic torque model [22]- [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported the impacts of motor and simulated motors, which were examined using motor current signature analysis (MCSA) and also through observation of magnetic flux density outside the motor [11]. Different approaches have been adopted to control the [4,[12][13][14][15] these approaches are explained below. Several experimental outcomes were provided to showing the impact of bearing and armature faults in single-phase induction motor [16].…”
Section: Introductionmentioning
confidence: 99%
“…"Among these three topologies, the Cascaded H-Bridge type is configured into modular unit with series connection to avoid balancing problem. However, the major problem with this type is that the requirement of complex transformer to provide isolated DC voltage supply for each H-Bridge Inverter circuit as present in [11][12][13][14]. "…”
Section: Introductionmentioning
confidence: 99%